Sulfated Galactan Derivative from Gracilaria fisheri Improves Histopathology and Alters Wound Healing-Related Proteins in the Skin of Excision Rats - Kamonwan Jongsomchai; Arnon Pudgerd; Waraporn Sakaew; Kanokpan Wongprasert; José Kovensky; Tawut Rudtanatip (Frontiers in Bioscience-Landmark)
Background: The biological activities of sulfated polysaccharides (SP) are well-documented, especially regarding wound healing. Sulfated galactan (SG), a type of SP extracted from the red seaweed Gracilaria fisheri, has been identified as having multiple therapeutic properties related to its wound healing capacity. Recent research indicates that degraded SG (DSG) from G. fisheri, when combined with octanoyl ester (DSGO), can improve wound healing in fibroblasts. However, the effectiveness of natural products in clinical settings often differs from in vitro results. This study aimed to develop and evaluate ointments containing DSG and DSGO for skin repair in an animal model. Methods: Twenty-four Wistar rats were divided into four groups: (1) normal control, (2) ointment control, (3) DSG ointment, and (4) DSGO ointment. After inducing full-thickness excision wounds, these ointments were applied to the wounds. Wound contraction rate, histopathology, and protein related wound healing expression were then elucidated. Results: Our findings showed that both DSG and DSGO ointments significantly enhanced wound closure compared to the control groups. Histopathological and biochemical analyses indicated increased extracellular matrix production and fibroblasts, marked by improved fibroblast activity, neovascularization, and collagen deposition. Furthermore, immunohistochemistry and immunoblot analysis revealed that the ointments altered the expression of Ki67, α-smooth muscle actin (α-SMA), E-cadherin, vimentin, collagen, and components of the Smad signaling pathway, all of which are crucial for wound healing. The results also suggested that the DSGO ointment was marginally more effective in promoting wound healing in this model. Conclusions: These results indicate that ointment supplemented with DSG and DSGO have the potential to enhance skin repair by improving histopathology and altering wound healing-related proteins.